Les menaces au droit à l’avortement et à l’autonomie des femmes enceintes - Lemonde, Lucie (Les Cahiers de droit, 2009)
Après un bref survol de l’histoire récente de la criminalisation de l’avortement au Canada, l’auteure présente les divers projets de loi privés touchant d’une façon ou d’une autre le droit à l’avortement, principalement le projet no C-484 sur l’homicide foetal, pour en saisir les conséquences sur le droit canadien et sur l’autonomie des femmes pendant leur grossesse. Ces projets de loi se situent à l’intérieur d’une stratégie des opposants à l’avortement qui a essentiellement pour objet de faire reconnaître en droit canadien un droit à la vie et à la sécurité aux foetus et de remettre en question le libre choix des femmes en la matière. Suit une discussion sur l’instrumentalisation du droit pénal à des fins de contrôle social de questions d’ordre éthique. Le texte se termine par une réflexion concernant l’intérêt de l’État dans la protection des foetus. L’auteure soutient que toute intervention étatique doit se faire dans le respect des droits constitutionnels des femmes, soit leur droit à la vie, à la santé et à la liberté.
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; amériques; approches et analyses; avortement; canada; cours; discipline; droit; droits des femmes*; justice reproductive; justice sociale; patriarcat; pol4102; premier cycle; périodes historiques; régions géographiques; science politique et droit; sexisme; systèmes d'oppressions; thématiques

Only words - MacKinnon, Catharine A. (Harvard University Press, 1993)
When is rape not a crime? When it's pornography--or so First Amendment law seems to say: in film, a rape becomes "free speech." Pornography, Catharine MacKinnon contends, is neither speech nor free. Pornography, racial and sexual harassment, and hate speech are acts of intimidation, subordination, terrorism, and discrimination, and should be legally treated as such. Only Words is a powerful indictment of a legal system at odds with itself, its First Amendment promoting the very inequalities its Fourteenth Amendment is supposed to end. In the bold and compelling style that has made her one of our most provocative legal critics, MacKinnon depicts a society caught in a vicious hypocrisy. Words that offer bribes or fix prices or segregate facilities are treated by law as acts, but words and pictures that victimize and target on the basis of race and sex are not. Pornography--an act of sexual domination reproduced in the viewing--is protected by law in the name of "the free and open exchange of ideas." But the proper concern of law, MacKinnon says, is not what speech says, but what it does. What the "speech" of pornography and of racial and sexual harassment and hate propaganda does is promote and enact the power of one social group over another. Cutting with surgical deftness through cases of harassment in the workplace and on college campuses, through First Amendment cases involving Nazis, Klansmen, and pornographers, MacKinnon shows that as long as discriminatory practices are protected as free speech, equality will be only a word.
Keywords: 1900-1999; 1990-1999; amériques; approches et analyses; cours; discipline; droit; histoire et politique; patriarcat; premier cycle; périodes historiques; régions géographiques; science politique et droit; sciences humaines; sciences sociales; sex1911; sexisme; sexualité; sofia; systèmes d'oppressions; thématiques; violences; états-unis; études de genres